Reasoning The Sharīʿa and Constructing a Proper Muslim Woman: Reflections on the Issue of Chinese Muslim Women's Haircut in Republican China - Li, Gang (Journal of Chinese Religions, 2022)
The major Muslim group in China, the Hui, discussed the issue of haircut for Muslim women in their own newspapers and magazines in the 1930s. Authors of those publica- tions include ordinary male and female Hui Muslims, Islamic clerics, and Muslim stu- dents from the new Islamic educational institutions. Based on various sources of Islamic jurisprudence (Sharia), the participants put forward varying opinions on the issue. In this article, I have investigated the debate on the Hui women's haircut by assessing how the debate started and developed, and what it meant for a Hui Muslim woman to cut or not to cut her hair in relation to the Shari a in the sociopolitical context of Republican China. I argue that different narratives tried to construct a proper Muslim woman, and furthermore, I also assess how Muslims in China during the Republican period defined their own identities of being Chinese and Muslim via debating on the "authentic" inter- pretation of the Shari' a Finally, Ipoint out that liberation of Chinese Muslim women is impossible unless there is comprehensive participation of them in the debat
CRIS-Team Scopus Importer:2024-12-16
Keywords: Hui Muslims; women in Islam; haircut; Shari' a; Republic of China